Answer:
The equation which describes the function g is:
![g(x)=-x+9](https://img.qammunity.org/2019/formulas/mathematics/college/45imjqq1r5p6fgt32lh1nixtj9nlerrvjn.png)
Explanation:
The graph of the function f(x) is given by:
![f(x)=x+9](https://img.qammunity.org/2019/formulas/mathematics/college/ffq5981x4ltb1cgytejdy5zkelrurk0k6j.png)
Now, we know that the transformation of the function f(x) when the graph is shifted across the y-axis then it is given by:
f(x) → f(-x)
This means that:
g(x)=f(-x)
i.e.
g(x)= -x+9
Hence, the equation which will represent the graph of the function g(x) is given by:
![g(x)=-x+9](https://img.qammunity.org/2019/formulas/mathematics/college/45imjqq1r5p6fgt32lh1nixtj9nlerrvjn.png)